The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/j.0022-0337.2003.67.12.tb03727.x
|View full text |Cite
|
Sign up to set email alerts
|

The American Academy of Developmental Medicine and Dentistry: Eliminating Health Disparities for Individuals with Mental Retardation and Other Developmental Disabilities

Abstract: Recent reports by Special Olympics International and the U.S. Surgeon General have revealed significant disparities and unmet health needs encountered by persons with mental retardation and other developmental disabilities (MR/DD). Factors contributing to these disparities include deinstitutionalization, increased survival of individuals with MR/DD, lack of appropriately trained providers, and inadequate financing of dental services. To address these problems, a group of academically oriented dentists and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 10 publications
0
40
0
3
Order By: Relevance
“… 6 Their ability to physically access the dental clinics and offices, along with their ability to afford the cost of the treatment and inadequate financing for dental treatment, may hinder their access to dental clinics. 6 , 9 12 Moreover, the preparedness and willingness of dental care providers to treat patients with special needs may impact access and thus their oral health. 1 , 3 , 13 …”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“… 6 Their ability to physically access the dental clinics and offices, along with their ability to afford the cost of the treatment and inadequate financing for dental treatment, may hinder their access to dental clinics. 6 , 9 12 Moreover, the preparedness and willingness of dental care providers to treat patients with special needs may impact access and thus their oral health. 1 , 3 , 13 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Because this issue has an impact on the oral health quality of patients with special needs, many studies have pointed out dental students’ lack of attempts to treat patients with special needs and have documented that the predoctoral curricula for treating patients with special needs are inadequate. 9 , 18 Moreover, studies have documented that limited dental care providers offer to treat patients with special needs and there are few who are prepared to educate dental students to be more competent to treat these patients in the future. 9 , 19 Furthermore, the more experience dental students have with the patients with special needs, the more able and willing they are to handle these patients.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of oral health in persons with developmental disabilities is prevalent and a concern to health professionals . Several studies have shown that oral health is important to maintain overall systemic health .…”
Section: Introductionmentioning
confidence: 99%